Consumer Choices: Impact of Advertising, Promotions, and Brand Image in Simpati Data Packages.: Pilihan Konsumen: Pengaruh Iklan, Promosi Penjualan, dan Citra Merek pada Pengguna Paket Data Simpati. - Mohammad Nafi Hartanto; Mudji Astuti (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative research aimed to investigate the individual and combined effects of advertising, sales promotion, and brand image on purchase decisions among consumers in Dusun Kedurus, Desa Kepatihan, Tulangan, Sidoarjo. A sample of 30 respondents was surveyed using questionnaires, and data were analyzed through multiple linear regression using SPSS 18.0. The findings revealed that advertising, sales promotion, and brand image had a partial and positive influence on purchase decisions. Moreover, when considered simultaneously, these factors collectively played a significant role in shaping consumers' purchase decisions. This study provides valuable insights for marketers and businesses in enhancing their marketing strategies to effectively influence consumer purchase behavior. Highlights: The study explores the impact of advertising, sales promotion, and brand image on consumer purchase decisions. Quantitative research with a sample of 30 respondents in a specific location provides valuable insights. Findings emphasize the need for effective marketing strategies to influence consumer behavior. Keywords: Purchase decisions, Advertising, Sales promotion, Brand image, Consumer behavior